Tora! Tora! Tora! - Forrester, Larry; Oguni, Hideo 1904-1996; Kikushima, Ryuzo 1914-; Balsam, Martin 1919-1996; Cotten, Joseph 1905-1994; Marshall, E.G. 1914-1998; Whitmore, James; Robards, Jason; Yamamura, So 1910-2000; Mihashi, Tatsuya 1923-; Tamura, Takahiro; Tono, Eijiro 1907-1994; et al.
A dramatization which chronicles the bombing of Pearl Harbor from both the Japanese and American points of view